Persepsi Siswa terhadap Metode Mengajar Guru Pendidikan Agama Islam pada Siswa SMPN 3 Tanjung Medan - Ilham Ade Pratama; Mario Kasduri (EduInovasi: Journal of Basic Educational Studies, 2023)
This research aims to determine students' perceptions of Islamic Religious Education (PAI) teachers' teaching methods for students at SMPN 3 Tanjung Medan. This research method uses descriptive quantitative methods. The population of this study was 81 students who were Muslim at SMPN 3 Tanjung Medan. The sampling technique uses Total Sampling, therefore the population and sample have the same number, namely 81 students. Data were collected using an open questionnaire and a scale of students' perceptions of the teacher's teaching methods which were measured using a Likert scale. The data analysis method used is descriptive analysis. Based on the results of data analysis, the research results show that students' perceptions are in the categories of 32.1% dissatisfied, 30.8% satisfied, 27.2% very dissatisfied, and 9.9% very satisfied. Therefore, it can be concluded that the most dominant student perception is dissatisfied at 32.1% and the lowest perception category is very satisfied at 9.9%.